Analisis Implementasi Intervensi Gizi Spesifik dalam Penanganan Stunting di Puskesmas Wilayah Kabupaten Bengkulu Utara - Irwan Kurniawan; Misnaniarti Misnaniarti; Rostika Flora (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
District North Bengkulu is still designated as a focus district for integrated stunting reduction interventions. How to implement nutrition intervention in stunting management. The research uses qualitative methods with an exploratory evaluation study design. The research was carried out from March to June 2021. The main informant was the head of the public health center, nutritionist, midwife.. Secondary informant Head of the Nutrition Section of the Health Office. Handling stunting reduction with specific nutrition interventions, which began in 2017, has partially reached the target. Implementation has implemented effective communication, position, resources, bureaucracy starting from Health Office, Head of Puskesmas, Nutrition Officer, Coordinator Midwife and to pregnant women, breastfeeding mothers. Implementation of stunting reduction policies through specific nutrition interventions. Communication on the implementation of stunting reduction policies has been carried out in accordance with bureaucratic mechanisms. The available resources are sufficient, so that the application of the concept of specific nutrition interventions can be implemented. The disposition and structure of the bureaucracy within the Health Office has been running in accordance with the existing bureaucratic mechanisms, the implementation of policies can be carried out according to the objectives.Keywords: Policy, Stunting, Communication, Resources, Bureaucracy